Isi Piringku Sebagai Strategi Manajemen Diet Untuk Lansia Dengan Diabetes Melitus di RT 14 Kelurahan Jalan Gedang oleh Mahasiswa KKN S1 Fakultas Ilmu Kesehatan Universitas Dehasen - Dena Sentia; Deni Fitriani; Tristi Nanda; Tasya Dwi Damayanti; Dinda Pressella; Citra Tia Yudia; Tita Septi Handayani (Universitas Dehasen Bengkulu, 2026)
Diabetes Melitus is a health problem commonly experienced by the elderly and poses a risk of serious complications. Diet management based on the My Plate concept is one non-pharmacological intervention that can help control blood sugar levels safely and sustainably. This study aims to evaluate the effectiveness of applying the My Plate concept as a dietary management strategy in improving the knowledge, awareness, and behavior of elderly people with Diabetes Melitus in RT 14, Jalan Gedang Village, Bengkulu City. The study was conducted on 24 elderly people who participated in a one-day education program. Activities included health education on Diabetes Melitus, blood sugar screening using a glucometer, nutrition education based on Isi Piringku, distribution of guidance leaflets, and demonstrations on daily menu planning. Data were analyzed descriptively to assess changes in knowledge, eating patterns, health behaviors, and access to health services. Diet education based on Isi Piringku was effective in improving the knowledge, awareness, and behavior of elderly people with Diabetes Melitus. This program encouraged changes in healthy eating patterns, routine blood sugar checks, and the use of health services, thereby contributing to blood sugar control and the prevention of long-term complications.